Antibacterial activities of purified monolaurin obtained from enzymatic glycerolysis of palm kernel olein-stearin blend against Bacillus subtilis - Ngatirah, Ngatirah; Hidayat, Chusnul; Rahayu, Endang Sutriswati; Utami, Tyas (Applied Food Biotechnology, 2023)
Background and Objective: Monolaurin can be produced by enzymatic glycerolysis of a mixture of palm kernel olein-stearin (PKOo-PKS). Monolaurin has the ability as an antibacterial agent against both gram-positive and negative bacteria. Limited studies investigated the activity against bacteria of monolaurin on B. subtilis cell and spores. Therefore, this research aimed to study the effect of a purified monolaurin obtained from enzymatic glycerolysis of PKOo-PKS blend on growth, spore germination, cell surface hydrophobicity, and cell structure of B. subtilis FNCC 0060. Material and Methods: Monolaurin was produced using palm kernel-olein blend material under the best enzymatic glycerolysis conditions and purified using solvent (hydroalcoholic) method. The effect of a purified monolaurin on B. subtilis growth and spore germination was studied using nutrient broth. Analysis of cell surface hydrophobicity (CSH) was carried out using MATHS (microbial adhesion to hydrocarbons) assay, while the cell structure was observed using Transmission Electron Microscope (TEM). As an experimental design, the completely randomized design (CRD) was used, and each treatment was triplicated. Analysis of variance (ANOVA) and Duncan multiple range tests (DMRT) were used to analyze the data, which revealed a significant difference. Results and Conclusion: This result showed that purified monolaurin inhibited the growth of B. subtilis FNCC 0060. Meanwhile, the development of B. subtilis in nutrient broth with monolaurin at 100-5,000 ppm was slower than without. A higher concentration in the medium decreases the specific growth rate and increases the doubling time. Spores of B. subtilis FNCC 0060 in nutrient broth with monolaurin at 100-1,000 ppm concentration were delayed in germination up to seven days of incubation. The presence of monolaurin significantly reduces the percent adherence of bacterial cells. Furthermore, the cytoplasm of B. subtilis FNCC 0060 appeared to have shrunk considerably, causing cell cytoplasm damage and disorganization of the components.